2005
DOI: 10.1136/bjo.2005.074062
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of T-bet expression in peripheral blood mononuclear cells during Vogt-Koyanagi-Harada disease

Abstract: Aim: To test the hypothesis that T-bet expression is altered in patients with Vogt-Koyanagi-Harada (VKH) disease. Methods: Peripheral blood was withdrawn from 16 VKH patients before and after immunosuppressive treatment and from 16 healthy individuals. IFN-c, IL-2, and IL-4 in the serum and the supernatants of peripheral blood mononuclear cells (PBMC) cultured with or without phytohaemagglutinin (PHA) were measured by ELISA. T-bet mRNA and protein expression in PBMC cultured with or without PHA was detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…[7][8][9] Various studies have found that cytokines are crucial in the occurrence and development of VKH disease. 7,10,11 Upregulated expression of IFN-c, IL-17, TBX21, and RORct in peripheral blood mononuclear cells (PBMCs) was detected in active VKH patients, 10,[12][13][14] suggesting that Th1 and Th17 lymphocytes are associated with this disease.…”
mentioning
confidence: 99%
“…[7][8][9] Various studies have found that cytokines are crucial in the occurrence and development of VKH disease. 7,10,11 Upregulated expression of IFN-c, IL-17, TBX21, and RORct in peripheral blood mononuclear cells (PBMCs) was detected in active VKH patients, 10,[12][13][14] suggesting that Th1 and Th17 lymphocytes are associated with this disease.…”
mentioning
confidence: 99%
“…Despite this, most human data confirm a predominance of activated CD4 + T cells orchestrating the pathogenesis of noninfectious uveitis [96,[100][101][102]. Corroborating the animal data discussed earlier, studies in patients with intermediate uveitis, Behçet's uveitis and VKH have also demonstrated a predominance of Th1 cells expressing high levels of IL-2, IFN-g, IL-12 and the transcription factor Tbet [102][103][104][105][106][107]. Further indirect evidence for the CD4 + Th1 drive is the suppression of IFN-g and IL-12 production observed during clinical improvement of active uveitis [108,109].…”
Section: T-cell Subsets and Autoimmunitymentioning
confidence: 90%
“…Our previous study revealed that T-bet expression at the mRNA and protein levels is upregulated in Behcet's and Vogt-Koyanagi-Harada patients with active intraocular inflammation [8,9]. Salvati et al [25] found that T-bet expression was increased in the inflamed mucosa of patients with celiac disease.…”
Section: D) Original Magnifications ×400mentioning
confidence: 93%